Integration of watershed land Change Management and Slum Rehabilitation Efforts in Flood-Prone Areas - Josep Adiyono Kardipo; Abdi Sugiarto; Cut Nuraini (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Land use changes in the watershed (DAS) area of Tebing Tinggi City have increased the risk of flooding and contributed to the development of slum settlements in vulnerable zones. Uncontrolled urbanization and economic pressures have driven residential expansion along riverbanks, forcing communities to live in substandard environmental conditions. This study aims to analyze the integration of watershed land use change management with slum rehabilitation strategies to enhance regional resilience against flood disasters. The research employed a mixed methods approach, combining qualitative phenomenological studies with quantitative descriptive statistical analysis. The findings indicate that collaboration among spatial planning, environmental policy, and community participation is crucial in creating a sustainable and disaster-responsive watershed management model. Strategic recommendations are centered on strengthening cross-sector coordination and implementing policies based on spatial and social data.